Pengaruh Senam Lansia Terhadap Skala Insomnia di Kelurahan Sidodadi - Marwan, Marwan; Darmiati, Darmiati; Arfan, Farmin (Yayasan Mandar Indonesia, 2022)
Insomnia is a sleep disorder that is often experienced by the elderly. Sleep is a brain process that is needed by a person to function properly. Sleep does not mean a busy routine, sleep is important for health, emotional function, mental and safety. With increasing age there is a decrease in sleep hours, the need for sleep decreases from infancy to old age. The average healthy adult needs 7 hours of sleep at night. Sleep deprivation in the elderly has an effect on physical, cognitive abilities, and psychological disorders. Based on a preliminary study, it was found that 23 elderly people experienced insomnia. Symptoms that often arise are difficulty sleeping at night, irritability, depression, anxiety, ulcers and difficulty start sleeping. One alternative to overcome insomnia is elderly exercise, this exercise will stimulate the HPA Axis mechanism to secrete melatonin, then from the hypothalamus it will be forwarded to the pituitary for the formation of beta endorphins and encephalins which can cause a relaxed condition. This study is a pre-experimental design research with the type of research